2005
DOI: 10.1016/j.yhbeh.2005.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Current research in amphibians: Studies integrating endocrinology, behavior, and neurobiology

Abstract: Amphibian behavioral endocrinology has focused on reproductive social behavior and communication in frogs and newts. Androgens and estrogens are critical for the expression of male and female behavior, respectively, and their effects are relatively clear. Corticosteroids have significant modulatory effects on the behavior of both sexes, as does the peptide neuromodulator arginine vasotocin in males, but their effects and interactions with gonadal steroids are often complex and difficult to understand. Recent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 104 publications
2
61
0
5
Order By: Relevance
“…Further, electrophysiological studies indicate that auditory cues stimulate hypothalamic neurons (Cheng et al, 1998). Similar phenomena in which vocal signals from a sender influence the physiology and neurobiology of a receiver have also been described in anuran amphibians Wilczynski et al, 2005). This is possible because in anurans, the central auditory system sends projections into the anterior and central thalamic nuclei, which relay auditory information into the anterior preoptic area as well as the ventral hypothalamus (reviewed in Wilczynski et al, 1993).…”
Section: Introductionmentioning
confidence: 73%
“…Further, electrophysiological studies indicate that auditory cues stimulate hypothalamic neurons (Cheng et al, 1998). Similar phenomena in which vocal signals from a sender influence the physiology and neurobiology of a receiver have also been described in anuran amphibians Wilczynski et al, 2005). This is possible because in anurans, the central auditory system sends projections into the anterior and central thalamic nuclei, which relay auditory information into the anterior preoptic area as well as the ventral hypothalamus (reviewed in Wilczynski et al, 1993).…”
Section: Introductionmentioning
confidence: 73%
“…Recent findings, however, indicate that relationships between calling activity and energy consumption may be complex (Carvalho et al 2008), emphasizing the need for more comprehensive observations of amphibian traits related to calling activity, such as incorporating not only social context, but also breeding period, locomotor behavior, and calling strategies. Intricately related to these two factors are hormones (Moore et al 2005;Wilczynski et al 2005;). Several studies have suggested that androgens and the neuropeptide arginine vasotocin (AVT) influence the calling behavior of frogs (Emerson & Hess 1996;Solis & Penna 1997;ten Eyck 2005), and higher androgen levels have been found in frogs exposed to conspecific vocalizations (Brzoska & Obert 1980;O'Bryant & Wilczynski 2010).…”
Section: Energetics and Endocrine Controlmentioning
confidence: 99%
“…The available results from different species are however not fully concordant, especially regarding the relationship of androgen levels and calling behavior (Moore et al 2005;Wells 2007). Evidence is more straightforward suggesting that AVT stimulates calling behavior (reviewed by Wilczynski et al 2005) and, more importantly, that it influences call features such as call patterning, call duration and pulse number (Marler et al 1995;Chu et al 1998;Klomberg & Marler 2000;Trainor et al 2003;Kime et al 2007). Taken together, the available evidence suggests that social interactions, hormones, and energetics are tightly linked to each other in numerous ways, and all of these factors have the potential to influence those features of frog vocalizations that are often considered relevant for taxonomic purposes.…”
Section: Energetics and Endocrine Controlmentioning
confidence: 99%
“…In diverse vertebrates, the preoptic area (POA) and amygdala (AMY) are necessary for the production of male-specific courtship and copulatory behaviors [7,26,43,57,62,93,96,97]. Motoneurons located in the brainstem or spinal cord innervate muscles required for courtship and copulatory behaviors.…”
Section: Introductionmentioning
confidence: 99%